2017
DOI: 10.5267/j.jpm.2017.5.001
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analyzing the impact of lean principles on organizational performance using ISM approach

Abstract: Existing literature on lean principles reveals the impact of lean principles on the organizational performance. During the past few years, the Indian manufacturing context has been competing with the global competitors directly to sustain their presence. One of the big motivations behind this is the steps taken in favor of replacing the policies and regulations for the manufacturing context by the government of India. In present, the manufacturing context is still far away to get the sustainable market because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This approach is the upgraded version of TISM and ISM (Rajan et al , 2020). The ISM is the qualitative analysis-based approach that provides the hierarchical model which generally referred as the well-defined model (Warfield, 1977; Kumar et al , 2017), whereas in the TISM the interpretation is done for every identified variable that further presents the model (digraph) based on iterations (Mittal et al , 2016, 2017; Sindhwani and Malhotra, 2017). In the ISM and TISM approach, the reachability matrix and the partitioning steps are same.…”
Section: Methodsmentioning
confidence: 99%
“…This approach is the upgraded version of TISM and ISM (Rajan et al , 2020). The ISM is the qualitative analysis-based approach that provides the hierarchical model which generally referred as the well-defined model (Warfield, 1977; Kumar et al , 2017), whereas in the TISM the interpretation is done for every identified variable that further presents the model (digraph) based on iterations (Mittal et al , 2016, 2017; Sindhwani and Malhotra, 2017). In the ISM and TISM approach, the reachability matrix and the partitioning steps are same.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of ISM technique is that the expert opinion gathered is consolidated and then structured using matrices and then modelled in the hierarchical form of levels with the relationships amidst levels being defined (Kumar, Kumar and Singh, 2017) . In recent years, ISM technique has been integrated with multiple MCDM approaches (Thakkar et al , 2005; Shahin et al , 2019b; Pourjavad et al , 2020) .…”
Section: Methodsmentioning
confidence: 99%
“…Drawing from a prodigious body of knowledge on lean implementation (Landsbergis et al, 1999;Parker, 2003;Delbridge, 2007;Demeter et al, 2009;Rahman et al, 2010;Yang et al, 2011;Kumar and Kumar, 2016;Shah et al, 2017;Kumar et al, 2017;Valente and Catarina, 2018) and LTP inculcation (Hines et al, 2004;Belekoukias et al, 2014;Aghakhani et al, 2016;Panwar et al, 2018;Iranmanesh et al, 2019), a direct effect is expected between LTP and OP. A conceptual framework highlighted by Liker (2004) in his book titled "The Toyota Way" puts forth a framework that highlights the critical indicators for the success of Lean Thinking like human resource management, workers' direction and involving employees in lean implementation focusing on teamwork.…”
Section: Lean Thinking In It Organizationsmentioning
confidence: 99%
“…Lean, with its initiation in the automobile industry, has been diligently implemented and researched across the manufacturing sector (Shah et al, 2017;Kumar et al, 2017;Valente and Catarina, 2018). A close review of literature from, Service Industry (Kim, 2013), the Retail Sector (Vlachos, 2015) and Healthcare and Pharmacy (Koeijera et al, 2014;Kelendar, 2020;Fiorillo et al, 2021) to name a few, indicate that lean is implemented in highvolume processes industries.…”
Section: Justification For It Industrymentioning
confidence: 99%
See 1 more Smart Citation